Design And Develop a Website Application For Waste Retribution Payment - Budiman, Ramdani; Hidayanti, Nur; Agustiani, Widia (Journal Collabits, 2024)
Dinas Lingkungan Hidup Kabupaten Serang carries out regional government affairs in the environmental sector in accordance with the Regent's vision, mission and programs outlined in the Regional Medium Term Development Plan (RPJMD). The problem that occurs in the waste levy payment process is that errors often occur in the data collection service for waste levy payments, then in the process of collecting data and recording payment reports, also in the process of recor`xding payments it can still be said to be less efficient because the levy officer has to write the data on proof of payment and wait for it to be recorded. on paper by the treasurer and then summarized in Microsoft Office Excel. The method used in this research is CodeIgniter (CI) for the information system being developed. The system design used in this research uses the waterfall method so that it is easier to develop and uses the Unified Modeling Language (UML) for visual system modeling. The results achieved after implementing this application made it easier for admins to overcome difficulties in inputting waste levy data which had previously been carried out at the Serang district environmental service. The conclusion obtained is that by using this waste levy application, it can support improvements in work so that the data input process is more effective and efficient. Waste levy data becomes more structured and well documented.